Proposals module call center operations in Manizales, Colombia - Ovalle Castiblanco, Alex (2016)
Call center are presented as a strategy that allows organizations to centralize business and delegate the organizational function of the relationship company - client. Its operation is based on the number of stations or modules in order to ensure better productivity of the system. This work intends to make a proposal for module used in the call center in the city of Manizales - Colombia, taking into account the standard technique Colombian NTC 1440 and international standards from the National Institute of safety and hygiene at work NTP 242 and NTP 602, with regard to ergonomic factors. The population was divided by a proportional stratified probability of cluster sampling. As a result it is proposed a flexible modular prototype, which has the conditions with which it is expected to achieve increases in productivity and reduction of injuries or illnesses that may occur when working on the modular system.